National Food Systems Summit Dialogues in Bangladesh, Ethiopia, and Viet Nam incorporate A4NH evidence around food systems for healthy and sustainable diets as part of the UN Food Systems Summit - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The national Dialogues helped Member States to develop pathways towards sustainable food systems and solicit expressions of intention to support these pathways from a broad range of stakeholders.